Amygdala-hypothalamus-brainstem circuits underlying cardiovascular responses associated with the limits of high-intensity endurance exercise - Yamanaka, K.; Kim, J.; Tsukioka, K.; Ezure, S.; Ichihara, H.; Pham, L. T.; Waki, H. (Frontiers in Physiology, 2025)
In athletic competitions, athletes continually challenge the limits of human performance. Exercise limitation refers to a state in which fatigue accumulates during prolonged activity, preventing the maintenance of the required power output despite maximal voluntary effort. High-intensity endurance exercise compromises muscle performance due to the accumulation of metabolic by-products in the peripheral tissues. Sympathetic nerve activation during exercise increases blood flow to the working muscles and aids in fatigue-inducing substance removal. However, excessive sympathetic activity may lead to peripheral muscular vasoconstriction, limiting exercise capacity. The present review explored the roles of the central autonomic regions, including the central nucleus of the amygdala (CeA), the paraventricular nucleus of the hypothalamus (PVN), and nucleus tractus solitarii (NTS) of the medulla in endurance limitation. The CeA is selectively activated during high-intensity exercises and contributes to the sympathetic drive. CeA lesions prolong exercise duration and delay blood pressure surges before exhaustion, suggesting that the CeA may act as a central "brake" on performance. Moreover, the co-activation pattern of the CeA-PVN-NTS circuits appears to shift dynamically depending on the exercise intensity. Understanding this emotion-autonomic circuits may provide new insights into exercise limitation and suggest novel strategies for enhancing endurance performance.